Determinan Obesitas pada Anak SD: Suatu Review Penelitian - Siti Rukayah (Jurnal Persada Husada Indonesia, 2020)
Based on the 2013 Basic Health Research (Riskesdas), overweight and obesity in children aged 5 to 12 years were 10.8% and 8.8%, respectively. Obesity is caused by many factors, especially genetic and environmental factors. In developing countries, environmental factors play a major role in the problem of obesity. Obesity is one of the most significant risk factors for physical and psychological health. This paper is a review of the results of obesity research in elementary school age children from 10 research journals published from 2010 to 2020. This study is a content analysis with the search keyword being obesity in elementary school age children. The first analysis shows a summary of research results from 10 selected journals. Analysis for the results was carried out on the average of the same variables and indicators. Furthermore, a qualitative analysis of the results will be carried out which has not been accommodated in the results presented. The majority of obesity occurs in boys, aged < 9 years, only doing light to moderate activities. In addition, only half of elementary school-aged children eat breakfast. While knowledge about obesity is only half as high, attitudes towards obesity are fifty-fifty between positive and negative. In terms of walking activities to school, the percentage is still low and sleeping less than 7 hours is still a large percentage. And last but not least the percentage of hobbies playing smart phones is very large. Several variables that trigger obesity in elementary school children are lack of physical activity, large pocket money, and the hobby of playing gadgets.